Targeted Therapy as a Potential De-Escalation Strategy in Locally Advanced HPV-Associated Oropharyngeal Cancer: A Literature Review - Chitsike, Lennox; Duerksen-Hughes, Penelope J. (Frontiers in Oncology, 2021)
The treatment landscape of locally advanced HPV-oropharyngeal squamous cell carcinoma (OPSCC) is undergoing transformation. This is because the high cures rates observed in OPSCC are paired with severe treatment-related, long-term toxicities. These significant adverse effects have led some to conclude that the current standard of care is over-treating patients, and that de-intensifying the regimens may achieve comparable survival outcomes with lower toxicities. Consequently, several de-escalation approaches involving locally advanced OPSCC are underway. These include the reduction of dosage and volume of intensive cytotoxic regimens, as well as elimination of invasive surgical procedures. Such de-intensifying treatments have the potential to achieve efficacy and concurrently alleviate morbidity. Targeted therapies, given their overall safer toxicity profiles, also make excellent candidates for de-escalation, either alone or alongside standard treatments. However, their role in these endeavors is currently limited, because few targeted therapies are currently in clinical use for head and neck cancers. Unfortunately, cetuximab, the only FDA-approved targeted therapy, has shown inferior outcomes when paired with radiation as compared to cisplatin, the standard radio-sensitizer, in recent de-escalation trials. These findings indicate the need for a better understanding of OPSCC biology in the design of rational therapeutic strategies and the development of novel, OPSCC-targeted therapies that are safe and can improve the therapeutic index of standard therapies. In this review, we summarize ongoing research on mechanism-based inhibitors in OPSCC, beginning with the salient molecular features that modulate tumorigenic processes and response, then exploring pharmacological inhibition and pre-clinical validation studies of candidate targeted agents, and finally, summarizing the progression of those candidates in the clinic.